2020
DOI: 10.37868/hsd.v2i2.42
|View full text |Cite
|
Sign up to set email alerts
|

A meta-study on future work in information and communication technologies

Abstract: Not only have Information and Communication Technologies (ICT) advanced in rapid succession, but society has embraced these developments and implemented them in daily life. This adoption has not only affected our way of conducting routine activities, but also significantly modified the way we do things as well as the things we now do. At this junction, rather than how engineering should improve ICT, the appropriate question seems to be “what should ICT engineers focus on? This question involves not only the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…e connection to power is another constraint that may limit the use of the application. In this regard, it is worth noting that the electricity coverage index-ICEE-at the national level is 96.10 percent, with 99.59 percent in urban areas, and 84.84 percent in rural regions [13][14][15]. As a result, the availability of electrical energy in rural areas does not pose a genuine threat to the usage of mobile application.…”
Section: Introductionmentioning
confidence: 99%
“…e connection to power is another constraint that may limit the use of the application. In this regard, it is worth noting that the electricity coverage index-ICEE-at the national level is 96.10 percent, with 99.59 percent in urban areas, and 84.84 percent in rural regions [13][14][15]. As a result, the availability of electrical energy in rural areas does not pose a genuine threat to the usage of mobile application.…”
Section: Introductionmentioning
confidence: 99%
“…Another research found on image processing is found in [9] which like [12][13][14][15] helps the early diagnosis of breast cancer using image processing; within this research, we can find that it uses the technique of segmentation by texture; the images used as evidence are from a database, which has images of cancerous masses and microcalcifications manually labelled by experts. In [16][17][18], they carry out the identification of breast cancer using thermal images, perform a digital processing of the images, using a texture analysis of the images to identify, and extract all the regions of interest.…”
Section: Review Of Literaturementioning
confidence: 99%